Correction of the Nasal Ala - Locketz, Garrett D.; Franco, Alexa; Miller, Philip J. (Facial Plastic Surgery, 2022)
The alar–columellar relationship is an important concept for the rhinoplasty surgeon to master. The alar rim in particular is a critical component of the nasal tip, contributing to both overall symmetry and proportion of the nasal base. The retracted ala creates a displeasing aesthetic to the tip complex, distorts the nostril openings, and may have functional implications of the external nasal valve. While alar retraction can occur naturally or as the result of trauma, the majority of cases are post-surgical in nature. Many techniques have been described for correction of alar retraction, most of which require open rhinoplasty and many fail to add the soft tissue within the vestibule necessary to properly lower the alar margin. Herein, we present our experience with the auricular chondrocutaneous composite graft—a simple, reliable, and effective technique to correct moderate to severe alar retraction via either open or endonasal rhinoplasty.
Keywords: Alar Retraction; composite graft; auricular composite graft; cartilage graft; auricular composite graft